Comparison of Strength Training Programs with Different Contraction Types - Tas, Zeki; Karabağ, Sezgin (Progress in Nutrition, 2021)
Study Objectives: As one of the basic motoric characteristics, strength is the capacity required for the performance and perfection of techniques in several sports branches. Optimum gain can be achieved by following proper training methods according to the characteristic of the strength that is desired to be improved particularly in the youth. In this study, the effects of strength training programs with different contraction types on the muscular force were compared. Methods: Thirty-six sedentary individuals between the ages of 18-26 living in the province of Konya participated in the study. The participants with similar strength averages were divided into 3 groups as Concentric (CG), Eccentric (EG), and Static (SG) based on their one-repetition maximum (1RM) strength values (the weight they lifted for once but could not lift in the second repetition) measured. Strength values of the individuals in each group were measured by performing exercises appropriate to the type of contraction. Results: According to the results of these measurements, a difference was found between the total contraction scores of the groups of CG, EG, and SG (F=20.99; p <.01). Accordingly, the contraction scores of CG and EG were found to be significantly higher than the contraction scores of the SG. Moreover, a positive difference was found between the pre-test and post-test scores of the participants (F=290.23; p<.01) Also, the group-by-time interaction was found to be insignificant (F = 193.82; p>.0.5). Conclusion: As a result, it has been concluded that KG produces more power than EG and EG produces more force than SG.